Analisis Prior Knowledge Konsep Asam Basa Siswa Kelas XI SMA untuk Merancang Modul Kimia Berbasis REACT - Gazali, Fauzana; Yusmaita, Eka (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
This study is a define phase of 4D model used in Research and Development (R&D) that aims to explore initial concept of grade XI students on acid-base topic before studying the material. Instrument used in this study was a two-tiered diagnostic test in the form of multiple-choice questions with choice of reasons that consisted of 16 items. The test was given to 100 grade XI students from various schools in West Sumatra. Studentsâ answers were processed by grouping them into 3 categories: understand, have misconceptions and do not understand. Data were then analyzed descriptively by calculating the percentage of students learning difficulties in all of competency achievement indicators that had been compiled. The results showed that students had difficulty in understanding some concepts of acid base such as acid base theory of Arrhenius (75.2%), of Bronsted-Lowry (81.43%), and of Lewis (100%); pH (94.04%); and acid base ionization constant (97.33%). Results of this research are then used as a consideration in the development of acid-base module designed for grade XI Senior High School learning.